2019
DOI: 10.3389/fevo.2019.00316
|View full text |Cite
|
Sign up to set email alerts
|

Monarch Butterfly Conservation Through the Social Lens: Eliciting Public Preferences for Management Strategies Across Transboundary Nations

Abstract: Monarch Conservation Through the Social Lens this research reveal that to maximize potential support amongst urban residents in the monarch's breeding range, a conservation strategy for the monarch butterfly should be led by not-for-profit organizations, should strive for transboundary cooperation, and should include the communication of anticipated ecological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 92 publications
(107 reference statements)
0
16
0
Order By: Relevance
“…Finally, the Monarch butterfly is a complex social-ecological system in which actions and perceptions from different stakeholders may play a determinant role in conservation strategies' support and success. Research is undergoing to couple the MOBU-SDyM and the lessons we learned here with previous social research (Solis-Sosa et al, 2019) to give policymakers the necessary tools to conserve the Monarch Butterly's eastern migratory phenomenon for generations to come.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, the Monarch butterfly is a complex social-ecological system in which actions and perceptions from different stakeholders may play a determinant role in conservation strategies' support and success. Research is undergoing to couple the MOBU-SDyM and the lessons we learned here with previous social research (Solis-Sosa et al, 2019) to give policymakers the necessary tools to conserve the Monarch Butterly's eastern migratory phenomenon for generations to come.…”
Section: Discussionmentioning
confidence: 98%
“…A recent analysis (Solis-Sosa et al, 2019), which we use in this paper, identified that, in general, urban residents across North America are more willing to pay for a given conservation strategy if it is led by an international NGO that distributes its restoration activities across the entire Monarch range and provides donors with a probability of reaching the conservation target, hereafter, program success. Also, donors were more willing to pay for a strategy when the overwintering monarch colonies area was small.…”
Section: Social Domainmentioning
confidence: 99%
“…We modelled the social domain as the proportion of potential donors supporting a milkweed restoration strategy under a specific conservation context defined by the simulated overwintering colonies' current overwintering area and trend. We used behaviour models obtained from the discrete choice experiment (DCE) by Solis-Sosa et al (2019), in which they explored how respondents' utility changed based on a series of strategic-level attributes of a Monarch's conservation strategy. The utility is defined as the weight of outcomes in making a decision (Ariely et al, 2003), or the level of short-term happiness derived from a specific material or immaterial good (Kimball & Willis, 2006).…”
Section: Social Domainmentioning
confidence: 99%
See 2 more Smart Citations